A rapid quantification method for tissue Na+ and K+ concentrations in salt-tolerant and susceptible accessions in Vigna vexillata (L.) A. Rich. (2nd January 2017) - Iseki, Kohtaro; Marubodee, Rusama; Ehara, Hiroshi; Tomooka, Norihiko
Abstract: A rapid quantification method for leaf sodium (Na + ) and potassium (K + ) concentrations was developed using a compact ion meter. Leaf ion concentrations were evaluated for species of Vigna vexillata (L.) A. Rich. after two weeks of treatment with 0–200 mM of sodium chloride. To compare the ion extraction efficiency, extraction solutions of distilled water and ammonium acetate were tested. The ion concentrations of extracts obtained by both solutions were measured using an ion meter, and the values were validated using ion chromatography. For both extraction solutions, the ion meter values were highly correlated with those of the ion chromatograph. However, correlations between ion meter and chromatograph values were largely different for Na + and K + . The rapid quantification of ion concentrations using an ion meter developed in this study was successfully utilized for evaluating differences in leaf Na + concentrations, K + concentrations, and K + /Na + ratio in species of V. vexillata .